Pemasaran di Perguruan Tinggi - Prabowo, Sugeng Listyo (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2005)
Higher education (university) as non profit institution service as well as another institution extremely need marketing. In this competitive era and required highly independency, the existence of customer is necessary. For this reason, management in university have to prove and build image in society that his institution able to fulfill the need and the hope of the society. Marketing in higher education mostly understood as selling and promotion were as marketing is more widely than about of two terminology above mention. Misunderstanding of marketing as usually happen university became